PENGEMBANGAN EKONOMI MASYARAKAT DESA MELALUI PENGUATAN SDM - Azriadi Tanjung (KOLONI, 2022)
One of the characteristics of village communities that are very identical is that generally their source of income depends on nature and the seasons. The economy in the village tends to be slow and not developing, the natural potential possessed is actually very large but the quality of human resources owned has not been able to keep up with these extraordinary natural resources. This study aims to describe how strategic steps in developing the economy of rural communities through strengthening human resources. This research uses descriptive qualitative methods. The results of this study show that the economic development of rural communities through strengthening human resources by: 1) carrying out e-marketing training and skills, 2) optimizing the role of BUMdes, and 3) developing the potential of tourism villages. Keywords: Economy, Village, Human Resources